Growth of Ag icosahedral nanocrystals on a SrTiO3(001) support - Silly, F; Castell, M; American Institute of Physics (2005)
We have investigated the structure and morphology of self-assembled silver nanocrystals supported on a SrTiO3(001)-(2x1) substrate using scanning tunneling microscopy. Ag forms nanocrystals with five-fold symmetry which have an icosahedral shape. Nanocrystals with point, edge, and face orientation (five-fold, two-fold, and three-fold symmetry, respectively) have been studied. The images of these nanocrystals allow a crystallographic identification of the supported shape of the icosahedral form.